An Environmental Scan of Canadian Quality Metrics for Patients on In-Center Hemodialysis. (December 2020) - Blum, Daniel; Thomas, Alison; Harris, Claire; Hingwala, Jay; Beaubien-Souligny, William; Silver, Samuel A.
Background: Quality metrics or indicators help guide quality improvement work by reporting on measurable aspects of health care upon which improvement efforts can focus. For recipients of in-center hemodialysis (ICHD) in Canada, it is unclear what ICHD quality indicators exist and whether they adequately cover different domains of health care quality. Objectives: To identify and evaluate current Canadian ICHD quality metrics to document a starting point for future collaborations and standardization of quality improvement in Canada. Design: Environmental scan of quality metrics in ICHD, and subsequent indicator evaluation using a modified Delphi approach. Setting: Canadian ICHD units. Participants: Sixteen-member pan-Canadian working group with expertise in ICHD and quality improvement. Measurements: We classified the existing indicators based on the Institute of Medicine (IOM) and Donabedian frameworks. Methods: Each metric was rated by a 5-person subcommittee using a modified Delphi approach based on the American College of Physicians/Agency for Healthcare Research and Quality criteria. We shared these consensus ratings with the entire 16-member panel for additional comments. Results: We identified 27 metrics that are tracked across 8 provinces, with only 9 (33%) tracked by multiple provinces (ie, more than 1 province). We rated 9 metrics (33%) as "necessary" to distinguish high-quality from low-quality care, of which only 2 were tracked by multiple provinces (proportion of patients by primary access and rate of vascular access-related bloodstream infections). Most (16/27, 59%) indicators assessed the IOM domains of safe or effective care, and none of the "necessary" indicators measured the IOM domains of timely, patient-centered, or equitable care. Limitations: The environmental scan is a nonexhaustive list of quality indicators in Canada. The panel also lacked representation from patients, administrators, and allied health professionals, with more representation from academic sites. Conclusions: Quality indicators in Canada mainly focus on safe and effective care, with little provincial overlap. These results highlight current gaps in quality of care measurement for ICHD, and this initial work should provide programs with a starting point to combine highly rated indicators with newly developed indicators into a concise balanced scorecard that supports quality improvement initiatives across all aspects of ICHD care. Trial Registration: not applicable.